Preferência alimentar e desenvolvimento de Cerotoma arcuata (Olivier) (Coleoptera: Chrysomelidae) em soja - Boiça Júnior, Arlindo Leal [UNESP]; Souza, Bruno Henrique Sardinha De [UNESP]; Costa, Eduardo Neves [UNESP]; Ferreira, Phelippe Sant'anna Honório [UNESP] (Escola de Agronomia e Engenharia de Alimentos/UFG, 2014)
Considering the increasing importance of Cerotoma arcuata in the last years, due to the economical losses caused on soybean crop, absence of insecticides registered in Brazil and lack of information about resistant cultivars, this study aimed to assess the feeding preference of adults and postembryonic development of C. arcuata on soybean cultivars and breeding line, in an attempt to find potential sources of resistance. The BRSMG 750 SRR, M-SOY 7908 RR and P 98Y30 RR commercial cultivars and the PI 274454 breeding line (used as the resistance standard from results obtained with Diabrotica speciosa) were used. In both the free-choice and no-choice feeding preference test, the attractiveness in different times, after releasing the adults, and the leaf area consumed at the end of the experiment were evaluated. In the antibiosis assay, the period and viability of the postembryonic development, weight of adults, sex ratio and longevity of adults without feeding were assessed. Overall, there were no differences in the attractiveness of the adults and leaf area consumed between the soybean cultivars and breeding line. Only the longevity of adults was longer on the PI 274454 breeding line and shorter on the BRSMG 750 SRR cultivar. The soybean commercial cultivars did not present resistance of the non-preference for feeding or antibiosis kinds to C. arcuata, and the PI 274454 breeding line must not be used as a resistance standard in resistance assays against this species.

Diante da crescente importância de Cerotoma arcuata nos últimos anos, devido aos prejuízos econômicos causados à cultura da soja, ausência de inseticidas registrados no Brasil e escassez de informações a respeito de cultivares resistentes, este trabalho objetivou avaliar a preferência alimentar de adultos e o desenvolvimento pós-embrionário de C. arcuata, em cultivares e linhagem de soja, visando a encontrar possíveis fontes de resistência. Utilizaram-se as cultivares comerciais BRSMG 750 SRR, M-SOY 7908 RR e P 98Y30 RR e a linhagem PI 274454 (padrão de resistência a partir de resultados com Diabrotica speciosa). No teste de preferência alimentar com e sem chance de escolha, foi avaliada a atratividade em diferentes tempos, após a liberação dos adultos, e a área foliar consumida, ao final do experimento. No teste de antibiose, foram avaliados o período e a viabilidade de desenvolvimento pós-embrionário, massa de adultos, razão sexual e longevidade de adultos sem alimento. Em geral, não houve diferenças na atratividade para os adultos e área foliar consumida entre as cultivares e linhagem de soja. Apenas a longevidade dos adultos foi maior na linhagem PI 274454 e menor na cultivar BRSMG 750 SRR. As cultivares comerciais de soja não apresentaram resistência dos tipos não preferência para alimentação ou antibiose a C. arcuata, e a linhagem PI 274454 não deve ser utilizada como padrão de resistência, em testes de resistência a esta espécie.
Feeding preference and development of Cerotoma arcuata (Olivier) (Coleoptera: Chrysomelidae) on soybean
Keywords: Glycine Max (L.) Merril; resistência de plantas; vaquinha-preta-e-amarela; Glycine max (L.) Merril; host plant resistance; leaf beetle